Multipartite interactions of Aphis (Toxoptera) and their associated symbionts - Guidolin, Aline Sartori (2016)
Insect-symbiont interactions have many bioecological consequences to the host. Their relationships expand through a complex network that includes other microorganisms, interactions with the environment and other trophic levels. An extensive literature has been produced on bacterial symbionts and aphids, especially for polyphagous aphids from North America and Europe, such as Acyrthosiphon pisum (Harris). They indicated symbionts influence host nutrition, heat tolerance, defense against natural enemies, virus transmission, host plant exploitation, among others. However, the outcome from host-symbiont interactions is context-dependent, with the expressed phenotype depending on intra and interspecific variations, symbiont strain, and biotic/abiotic stimuli. We explored the interaction between aphids and associated symbionts, aiming to contribute to this field by exploring new aphid systems, and focused on Aphis (Toxoptera) citricidus (Kirkaldy) and associated microbiota. We investigated the influence of the feeding habits on symbiont diversity in an oligophaogus, A. citricida, as compared to a polyphagous species, Aphis (Toxoptera) aurantii Boyer de Fonscolombe. We employed several approaches (biological, metagenomics, genomic, and proteomic) to investigate i) the impact of host plants on fitness traits and primary symbiont abundance in the oligophagous and polyphagous species, ii) differences in the draft genome of the primary aphid symbiont between A. citricidus and A. aurantii, iii) the influence of host plant in secondary symbiont distribution in A. citricidus, iv) secondary symbiont richness and abundance in both aphids, and investigate the effects of Spiroplasma infections v) in the fitness traits, vi) transcriptome and ii) proteome of A. citricidus when reared on two host plants (sweet orange and orange jasmine). Our data indicated that sweet orange is a better host plant than orange jasmine for both aphids, and that A. citricidus was more negatively affected by lower-quality host than A. aurantii. A. citricidus and A. aurantii had different strategies regarding Buchnera growth and the use of food in different stages of development. We observed differences in the draft genome of Buchnera associated to A. citricidus and A. aurantii. Host plant affected secondary symbiont abundance, but Spiroplasma was the most abundant symbiont in both aphids. Spiroplasma had neutral effects on A. citricidus biology, but affected host transcriptome and proteome. The host plant affected gene expression of A. citricidus, but the effect was dependent on Spiroplasma infection. Transcriptome analysis indicated Spiroplasma down-regulated aphid immune response genes on sweet orange, while regulating an entire different set of genes on orange jasmine, mainly chaperonins. Gene transcription of A. citricidus was strongly influenced by the host plant. But while a large number of transcripts were up-regulated in uninfected aphids in sweet orange as compared to orange jasmine, the same set of genes had an opposite pattern of expression in Spiroplasma-infected aphids. Comparative proteomic analysis of Spiroplasma-infected and uninfected aphids on sweet orange and orange jasmine demonstrated regulation of a larger number proteins on orange jasmine than on sweet orange. Spiroplasma down-regulated the immune response of aphids and up-regulated proteins related to nutritional processes when developing on a low-quality host plant, orange jasmine, while no such trend was observed on sweet orange.